"Liminal" Orthodoxies on the Margins of Empire: Twentieth-Century "Home-Grown" Religious Movements in the Republic of Moldova. Issue 1 (2nd January 2017) - Kapaló, James
Abstract : In the 20th century, the Russian Orthodox Church, the Romanian Orthodox Church, and the Soviet atheist state each pursued missions that attempted to transform Moldovans into loyal and trustworthy subjects and to integrate them into new state structures. This article explores the "liminal" character of Moldovan identities forged on the Russian and Romanian borderlands through the prism of Moldova's "home-grown" religious movements. Grass-roots movements led by charismatic and "trickster" religious figures "played" with dichotomies of the hidden and the revealed, innovation and tradition, and human and divine, succeeding in transforming the subject positions of whole segments of Moldovan peasant society. The resulting forms of "liminal" Orthodoxy have proved enduring, perpetually critiquing and transgressing canonical norms from the margins and subverting the discourses and narratives that seek to "harmonize" identities and to consolidate nation, state, and church in the Republic of Moldova.